Mesoporous silica nanoparticles trigger mitophagy in endothelial cells and perturb neuronal network activity in a size- and time-dependent manner - Orlando A (Dove Medical Press, 2017)
Antonina Orlando,1 Emanuela Cazzaniga,1 Maria Tringali,2 Francesca Gullo,3 Andrea Becchetti,3 Stefania Minniti,1 Francesca Taraballi,4,5 Ennio Tasciotti,4,5 Francesca Re1 1Nanomedicine Center, School of Medicine and Surgery, University of Milano-Bicocca, Monza, 2Department of Environmental Sciences, 3Department of Biotechnologies and Biosciences, University of Milano-Bicocca, Milan, Italy; 4Center for Biomimetic Medicine, Houston Methodist Research Institute (HMRI), 5Department of Orthopedics and Sports Medicine, Houston Methodist Hospital, Houston, TX, USA Purpose: Mesoporous silica nanoparticles (MSNPs) are excellent candidates for biomedical applications and drug delivery to different human body areas, the brain included. Although toxicity at cellular level has been investigated, we are still far from using MSNPs in the clinic, because the mechanisms involved in the cellular responses activated by MSNPs have not yet been elucidated.Materials and methods: This study used an in vitro multiparametric approach to clarify relationships among size, dose, and time of exposure of MSNPs (0.05–1 mg/mL dose range), and cellular responses by analyzing the morphology, viability, and functionality of human vascular endothelial cells and neurons.Results: The results showed that 24 hours of exposure of endothelial cells to 250 nm MSNPs exerted higher toxicity in terms of mitochondrial activity and membrane integrity than 30 nm MSN at the same dose. This was due to induced cell autophagy (in particular mitophagy), probably consequent to MSNP cellular uptake (>20%). Interestingly, after 24 hours of treatment with 30 nm MSNPs, very low MSNP uptake (<1%) and an increase in nitric oxide production (30%, P<0.01) were measured. This suggests that MSNPs were able to affect endothelial functionality from outside the cells. These differences could be attributed to the different protein-corona composition of the MSNPs used, as suggested by sodium dodecyl sulfate polyacrylamide-gel electrophoresis analysis of the plasma proteins covering the MSNP surface. Moreover, doses of MSNPs up to 0.25 mg/mL perturbed network activity by increasing excitability, as detected by multielectrode-array technology, without affecting neuronal cell viability.Conclusion: These results suggest that MSNPs may be low-risk if prepared with a diameter <30 nm and if they reach human tissues at doses <0.25 mg/mL. These important advances could help the rational design of NPs intended for biomedical uses, demonstrating that careful toxicity evaluation is necessary before using MSNPs in patients. Keywords: mesoporous silica nanoparticles, nanotoxicity, endothelial cells, neurons, brain